Effects of Cassia alata Linn on bowel function recovery following surgery for gynecological cancer: A randomized controlled trial. (December 2019) - Phutsisen, Jenwit; Kietpeerakool, Chumnan; Jampathong, Nampet; Chumworathayi, Bundit; Temtanakitpaisan, Amornrat; Aue-aungkul, Apiwat; Boontasaeng, Pornnapa
Highlights: Women with gynecologic cancer who undergo abdominal surgery are at high risk for developing postoperative ileus. Consumption of Cassia alata Linn hastens gastrointestinal function recovery after laparotomy in women with gynecologic cancer. This is the first randomized trial to investigate the effects of Cassia alata Linn consumption in the early period following surgery. Abstract: Background: Postoperative ileus is a common complication following abdominal surgery. This study was undertaken to determine the effectiveness and safety of Cassia alata Linn in stimulating gastrointestinal function recovery among women with gynecologic cancer who had undergone laparotomy for surgical staging or cytoreductive surgery. Methods: A total of 90 participants were randomly allocated to postoperative consumption of either Cassia alata Linn tea (n = 45) or warm water (N = 45). Outcomes of interest included time to first passage of flatus, time to first defecation, time to toleration of solid food, and ileus symptoms. Differences between the groups were measured as mean difference (MD) or odds ratio (OR) with 95% confidence interval (CI). Results: Women allocated to the Cassia alata Linn group had shorter times to first passage of flatus (MD −8.53; 95% CI −3.69, −13.38 h) and first defecation (MD −19.83; 95% CI −11.18, −28.48 h) compared with controls. There were no differences in terms of time to toleration of solid food (MD 0.26; 95% CI −2.13, 1.61 h) or ileus symptoms (OR 0.10; 95% CI 0.01, 1.94) between the two groups. Conclusion: Postoperative consumption of Cassia alata Linn hastens gastrointestinal function recovery after laparotomy in women with gynecologic cancer.